Impedance and parasitic capacitance analysis of SiC MOSFETs - Tan, Wei Jie (Nanyang Technological University, 2020)
Power electronic systems have benefited tremendously in power discrete devices in the past ten years. In the year 1970s, MOSFETs, which are known as Metal–Oxide–Semiconductor Field-Effect Transistors, as well as Insulated Gate Bipolar Transistors (IGBTs) in the 1980s, significantly allowed designs of compact high-efficiency systems, mainly due to the tremendously improved power gain. [1]